Hippocampal subfield morphology in regular hemodialysis patients. Issue 4 (17th September 2022) - Chen, Hui Juan; Qiu, Jie; Qi, Yonghui; Fu, Lili; Fu, Qingqing; Wu, Wenyuan; Dai, Ganmian; Chen, Feng
ABSTRACT: Background: Hippocampal alterations have been implicated in the pathophysiology of cognitive impairment in hemodialysis patients. The hippocampus consists of several distinct subfields, and the molecular mechanisms underlying cognition might be associated with specific hippocampal subfield volume changes. However, this has not yet been investigated in hemodialysis patients. This study aimed to explore volumetric abnormalities in hippocampal subfields in regular hemodialysis patients. Methods: High-resolution T1-weighted structural images were collected in 61 subjects including 36 hemodialysis patients and 25 healthy controls. A state-of-the-art hippocampal segmentation approach was adopted to segment the hippocampal subfields. Group differences in hippocampal subfield volumes were assessed in Python with a statsmodels module using an ordinary least squares regression with age and sex as nuisance effects. Results: Hemodialysis patients had significantly smaller volumes in the bilateral hippocampus ( P  < .05/2, Bonferroni corrected), cornu ammonis 1 (CA1), CA4, granule cell and molecular layer of the dentate gyrus, hippocampus–amygdala transition area and molecular layer of the hippocampus than healthy controls ( P  < .05/24, Bonferroni corrected). Hemodialysis patients also had lower volumes in the left hippocampal tail and right fimbria than healthy controls ( P  < .05/24, Bonferroni corrected). Hippocampal subfield volumes were associated with neuropsychological test scores, the duration of disease and hemoglobin levels. Conclusions: We found smaller hippocampal subfield volumes in hemodialysis patients, which were associated with impaired cognition, supporting their role in memory disturbance in the hemodialysis population. However, multiple clinical factors may have confounded the results, and therefore, the interpretation of these results needs to be cautious.